Mickey Mouse Sign on Bone Scan in the Monostotic Form of Paget's Disease Mimicking Osseous Metastasis - TUROĞLU, HALİL TURGUT; ÖZGÜVEN, SALİH; KESİM, SELİN; ERDİL, TANJU YUSUF; ÖNEŞ, TUNÇ (GALENOS YAYINCILIK, 2020)
Paget's disease is a chronic benign bone disease characterized by excessive and abnormal bone remodeling. Monostotic Paget's disease accounts for only 20% of the cases, and the monostotic form involving the vertebra with the Mickey Mouse sign is very rare. Herein, we report a case of suspected bony metastasis in the second lumbar vertebra that was diagnosed as Paget's disease because of the Mickey Mouse sign on bone scintigraphy, and the diagnosis was confirmed by biopsy. Therefore, bone scintigraphy may provide a positive contribution to the diagnosis, and may help to avoid unnecessary biopsy in cases with specific signs and patterns.
Keywords: Paget's disease; monostotic Paget's disease; spine; Mickey Mouse sign; technetium 99m-methylene diphosphonate bone scintigraphy; SPECT/CT; VERTEBRAE; CT